Solving the Mystery of Crypto’s Bubble - Sengar, Harsh (Ushus Journal of Business Management, 2021)
Blockchain is the vehicle on which cryptocurrencies run, and it can’t be regulated by any legal entity during its operation.The huge growth in various cryptocurrency segments in 10 years has created the controversy of an inevitable bubble. A bubble can be generated either by queer herd behaviour or logical secular movement. Traces of evident bubbles have been a certainty and they take the perceived valuation of crypto to figures far away from its true value. This sudden diversion can be lethal due to the illogical, irrational propensity of regular market participants. This study observes ten cryptos under surveillance from September 2014 to August 2019. The selected ten (Monero, Bitcoin, XRP Ripple, Litecoin, Dogecoin, Monacoin, Ethereum, Bytecoin, Digibite, Potcoin) cryptocurrencies were studied for the last five years using Right Tailed ADF Test. Prominent traces of the rational bubble in all the underlying cryptocurrencies were found and have been considered for the study.